Memorization activity and use of reinforcement in learning: content analysis from neuroscience and Islamic perspectives - Rahman, N.N.; Adli, D.S.H.; Saat, R.M.; Hashim, Z.I.M.; Bajuri, M.K.; Yusoff, M.Y.Z. (Asian Network for Scientific Information, 2011)
The field of neuroscience focuses on the nervous system. Activities of neurons, primary cells of the system, are responsible for all human behavior, e.g,. physical activities (such as movements) and complex mental activities (such as planning). These brain functions that neuroscience researches of different approaches have totally entrusted to the neurons are considered from the Islamic perspective as activities traversing across diverse issues, including matters pertaining to religious responsibilities of a Muslim. The current constraints due to compartmentalization of knowledge could lead to confusion and/or conflicts among students, educators and the Muslim community from the various conventional science streams. In addition, individuals with Islamic studies background have different understanding and usage of terms which are commonly difficult to explain to those educated in the conventional science stream. Non-comprehensive understanding of the two parties on specific issues could result in a clash of views, thus, leading to any arising problematic issues being unsuccessfully addressed. This study focused on the learning process, a general acquisition process for new information, behavior and/or capabilities and consequent processing by the nervous system. Through content analysis approach, systematically collected information of memorization activities and the use of reinforcements; two activities associated to the process of formal learning, was looked at from the perspectives of neuroscience and Islam. Memorization of al-Quran, a practice commonly implemented in Islamic studies education, was also focused on. Findings show that although from both neuroscience and Islamic perspectives memorization and the use of rewards have similar features, significant differences were also noted. © 2011 Asian Network for Scientific Information.